IGNAZ PHILIPP SEMMELWEIS - N. A. Makatsariya (Акушерство, гинекология и репродукция, 2016)
The article highlights historic aspects of medical and research work of the Hungarian obstetrician of the XIX century Ignaz Philipp Semmelweis.